“Affective Textures” of Body-oriented Perception in Contemporary Art - Venkova, Alina V. (Actual Problems of Theory and History of Art, 2024)
Research on affective experience as a cultural practice in the philosophy of art, aesthetics, and media theory, formed within the framework of the “affective turn,” allows us to identify new tools for analyzing hybrid forms of contemporary art. The theory of affect proposes such concepts as perception, vibration, embrace or grip, removal, separation, relaxation (J. Deleuze and F. Guattari), categorical affect, vitality affect, implicit form, intension, tropisms, gradients, resonance (B. Massumi), self-affectation, affective texture (M. Hansen), and affective atmosphere (S. Lowe). The concept of “affective texture”, which is the material base of body-oriented perception, reflects the direction of development of body-oriented, environmental art, installation art, and sound art. Sound art can be successfully studied in the context of the affective approach in the terminology of new materialism by K. Cox. M. Hansen shows the possibilities of the theory of affect on the material of media art in working with technically generated images that experience various distortions, resulting in a different visual, auditory, or tactile range from the natural one, which leads through technical mediation to self-affectation. A media image that includes an immersive effect has a capacity to “infect” the recipient with an unrepresentable and indivisible affect. The art works of Gregor Schneider, Mike Nelson, Roger Hiorns, Haegue Yang, Cecilia Vicuña, Anicka Yi, and Chagla Ilk allow us to apply the proposed terminology to describe poor verbalized states that are important for these artistic statements outside of the terminology and apparatus of the theory of representation. The technological foundation of such works gives rise to “affective textures” in the receptive response, bodily reactions-indices, partially amenable to description using the apparatus of the theory of affect. Based on an affective response, artistic mediums are able to capture and hold the not fully conceptualized and rationalized experience of immersion in art.
Keywords: affect; affective turn; affective texture; affective object; self-affectation; immersion